Floods and the City of San José, Costa Rica: The Crisis as a Driver for Technical and Political Networks - Guevara Víquez, Sofía (2025)
The article proposes to analyse the relationship between crisis, urban network and community organizing in the era of the Anthropocene, through the study of urban flooding in San José, the capital of Costa Rica. Based on qualitative data collection, we show on the one hand that the sewerage network of the Costa Rican capital was built up during the 20th century, through successive crises, transforming rivers into stormwater and wastewater collectors. The crisis is a driving force behind the development of the sewerage system, which reached its limits at the turn of the 21st century. Durning this time, when the metropolitan area has expanded significantly, the possibilities of physical interventions to make the system more fluid seem limited. The new crises thus become a driving force for a socio-political appropriation of the infrastructure, through the deployment of a citizen alert network on the Whatsapp platform at the scale of a segment of the system, the Ocloro River. These resilience practices do not consist of material interventions, but of political appropriation by the residents affected. The latter introduces new ways of discussing modes of managing the infrastructure and their renewal in an urban context that is under stress.